2018
DOI: 10.1017/ice.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Healthcare Personnel in Outpatient Settings: The Influence of Mandatory Versus Nonmandatory Influenza Vaccination Policies on Workplace Absenteeism During Multiple Respiratory Virus Seasons

Abstract: OBJECTIVE To determine the effect of mandatory and nonmandatory influenza vaccination policies on vaccination rates and symptomatic absenteeism among healthcare personnel (HCP). DESIGN Retrospective observational cohort study. SETTING This study took place at 3 university medical centers with mandatory influenza vaccination policies and 4 Veterans Affairs (VA) healthcare systems with nonmandatory influenza vaccination policies. PARTICIPANTS The study included 2,304 outpatient HCP at mandatory vaccination sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 35 publications
(59 reference statements)
0
41
1
1
Order By: Relevance
“…We identified 8 observational studies of moderate to lower moderate quality [19] , [20] , [21] , [22] , [23] , [26] , [27] , [30] , 5 of which found a vaccine benefit to HWs or employers and 3 which found no benefift or inconclusive results. A study in a large Italian hospital found an increase in absenteeism [19] from 2.99 days/person (outside of flu season) to 5.06 days/person (during flu season), which translated to 11,000 attributable absent days/year.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 8 observational studies of moderate to lower moderate quality [19] , [20] , [21] , [22] , [23] , [26] , [27] , [30] , 5 of which found a vaccine benefit to HWs or employers and 3 which found no benefift or inconclusive results. A study in a large Italian hospital found an increase in absenteeism [19] from 2.99 days/person (outside of flu season) to 5.06 days/person (during flu season), which translated to 11,000 attributable absent days/year.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The study also found that vaccinated HWs had fewer excess sick days compared to non-vaccinated HWs (1.45 days/person vs. 2.09). A retrospective study in the United States (4063 subjects) compared absenteeism in mandatory vs. non-mandatory vaccination sites [21] and found that vaccinated HWs had fewer symptomatic days absent {2012/2013, OR = 0.82 (95% CI, 0.72–0.93); 2014/2015, OR = 0.81 (95% CI, 0.69–0.95)} and concluded that mandatory vaccination would reduce symptomatic absenteeism.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…79 Despite its modest VE, the benefits of vaccination to HCP are clear, with reductions in both illness and absenteeism. 80 Overall evidence supportsdand the CDC recommendsdaiming for universal annual immunization of HCP. 81 Naturally, there is interest in whether HCP vaccination benefits their patients.…”
Section: Influenza Vaccinementioning
confidence: 92%